ANALISIS PELAKSANAAN MANAJEMEN RISIKO DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Rachmawati Yulianingtyas; Putri Asmita Wigati; Anneke Suparwati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Risk Management is a proactive approach to identify, assess and prioritize risks in order to eliminate or minimalize their impact. This program is conducted in hospital patient safety efforts in order to control risks and anticipating incidents inherent in any patient services. Sultan Agung Islamic Hospital (RSISA) is a private hospital in Semarang with type B that is belongs to Waqf Sultan Agung Agency Foundation (YBWSA) which is located in JL. Raya Kaligawe Km 4. The process of health care to patients in hospital is not separated to the potential errors that can lead to the incidents. This research done by looking at the implementation of the risk management from Mandate and Commitment, Planning, Implementation, Monitoring and Review, Improvement, and Coordination Process. This type of research is descriptive analytic withqualitative approaches. There are 5 (five) persons as subject’s research. Triangulation is done by using triangulation of sources and observations. The results showed that Mandate given by the KMKP to all units; the Commitment from KMKP and the units are still lacking; The Planning done by KMKP with the help from the units, planning goals and objectives is based on situations and contidions that decvelop in the hospital, the elections of the team who responsible for implementating risk management in each units was done in the early implementation, the method of risk management is FMEA, there is no SOP that can translate the real risk management activities, there are budgetting activities for funds and infrastucture to facilitate the risk management implementation; in the implementation, there are many obstacles from human resources, funds and the process; monitoring activities performed through the reporting process 3 monthly but there is still much delay and there no effort to risk assessment; continuously improvement with the principles of PDCA is done only for the unit which has the risks are prioritaized and not for the orther units.; in coodination process, risk management meeting has been vacuum since mid-2015, consultancy and communication process went well. In conclusion, the implementation of risk management in RSISA are still not well. Our suggestion, RSISA need to raise the commitment again and equalize the perception of the concept of risk management itself.